Underwater Localization and Mapping Based on Multi-Beam Forward Looking Sonar - Cheng, Chensheng; Wang, Can; Yang, Dianyu; Liu, Weidong; Zhang, Feihu (Frontiers in Neurorobotics, 2022)
SLAM(Simultaneous Localization And Mapping) plays a vital role in navigation tasks of AUV(Autonomous Underwater Vehicle). However, due to a vast amount of image sonar data and some acoustic equipment's inherent high latency, it is a considerable challenge to implement real-time underwater SLAM on a small AUV. This paper presents a filter-based methodology for SLAM algorithms in underwater environments. First, a multi-beam forward-looking sonar(MFLS) is utilized to extract environmental features. The acquired sonar image is then converted to sparse point cloud format through threshold segmentation and distance-constrained filtering to solve the calculation explosion issue caused by a large amount of original data. Second, based on the proposed method, the DVL, IMU, and sonar data are fused, the Rao-Blackwellized particle filter(RBPF)-based SLAM method is used to estimate AUV pose and generate an occupancy grid map. To verify the proposed algorithm, the underwater vehicle is equipped as an experimental platform to conduct field tasks in both the experimental pool and wild lake respectively. Experiments illustrate that the proposed approach achieves better performance in both state estimation and suppressing divergence.